ANALYSIS OF INFLUENCE FACTORS ACCOUNTING CONSERVATISM - Tegar Pramana; Iwan Fakhruddin; Hadi Pramono; Ira Hapsari (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This study aimed to determine the effect of financial distress, growth opportunities, institutional ownership, managerial ownership, profitability, leverage, and company size on accounting conservatism. The samples used in this study were companies in the consumer non-cyclical sector in the food & staples retailing, beverages, and processed foods sub-sector in 2017-2021, with 100 samples. The data analysis technique used is panel data regression analysis. Using three stages of the test, namely the preliminary test, which will determine the model used through the chow test, the Breush test and pagan Lagrangian multiplier, and the Hausman test. Based on the results of the three preliminary tests, this research will use a random effect model to examine the relationship between variables. Then the diagnostic tests, namely heteroscedasticity, and autocorrelation, are continued with hypothesis testing. The results of this study indicate that the variables of financial distress, profitability, and leverage positively affect accounting conservatism. At the same time, growth opportunities variables, institutional ownership, managerial ownership, and company size do not affect accounting conservatism.